2018
DOI: 10.17221/146/2016-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Cold hardiness of peach flowers at different phenological stages

Abstract: At the colder peach production regions it is important to know the cold hardiness of peach cultivars at different phenological stages of flowering. In our experiment, artificial freezing tests were conducted in a climate chamber in five selected years between the period of 2007 and 2016 to determine the freeze tolerance of generative organs of three peach cultivars (‘Venus’, ‘Redhaven’, ‘Piroska’) at different phenological stages of bloom. Based on the results of the laboratory freezing tests LT<sub>50&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This study showed the same S-shaped curve as reported in previous studies [42]. Lethal temperature predictions due to electrolyte leakage have been shown to overestimate cold tolerance by predicting relatively low lethal temperatures at low temperatures rather than actual plant regeneration [10,13,43]. However, since this study aimed to compare and predict the lethal temperature between plants, it was concluded that the cold tolerance comparison between plants was possible because the experiment was carried out under the same conditions.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This study showed the same S-shaped curve as reported in previous studies [42]. Lethal temperature predictions due to electrolyte leakage have been shown to overestimate cold tolerance by predicting relatively low lethal temperatures at low temperatures rather than actual plant regeneration [10,13,43]. However, since this study aimed to compare and predict the lethal temperature between plants, it was concluded that the cold tolerance comparison between plants was possible because the experiment was carried out under the same conditions.…”
Section: Discussionsupporting
confidence: 74%
“…The numerical expression of low-temperature tolerance levels is often required in temperature stress studies. The relationship between low-temperature stress and electrolyte leakage has the form of an S-shaped response curve, and the temperature at which 50% of electrolyte leakage begins to be observed is defined as the median lethal temperature, LT 50 [10,13,14]. Estimation of the LT 50 has been attempted primarily using linear interpolation, the logistic model, and the Gompertz model [15].…”
Section: Introductionmentioning
confidence: 99%
“…The artificial freezing experiments were performed in the climate chamber Rumed 3301 (Rubarth Apparate GmbH, Laatzen, Germany), according to the method and protocol developed on the Department of Pomology (Szalay et al, 2018(Szalay et al, , 2019. Four or five appropriate freezing temperatures were used at each testing date, according to the rate of dormancy.…”
Section: Methodsmentioning
confidence: 99%
“…A number of authors have studied the relationship between spring frost and peach and nectarine phenological phase [4,12]. Other researchers [11] have determined that phenological and pomological characteristics are important for introduced nectarine cultivars adaptation.…”
Section: Introductionmentioning
confidence: 99%